Complete sequence and comparative analysis of the mitochondrial genome of the rare and endangered Clematis acerifolia, the first clematis mitogenome to provide new insights into the phylogenetic evolutionary status of the genus - Liu, Dan; Qu, Kai; Yuan, Yangchen; Zhao, Zhiheng; Chen, Ying; Han, Biao; Li, Wei; El-Kassaby, Yousry A.; Yin, Yangyang; Xie, Xiaoman; Tong, Boqiang; Liu, Hongshan (Frontiers in Genetics, 2023)
Clematis is one of the large worldwide genera of the Ranunculaceae Juss. family, with high ornamental and medicinal value. China is the modern distribution centre of Clematis with abundant natural populations. Due to the complexity and high morphological diversity of Clematis, the genus is difficult to classify systematically, and in particular, the phylogenetic position of the endangered Clematis acerifolia is highly controversial. The use of the mitochondrial complete genome is a powerful molecular method that is frequently used for inferring plants phylogenies. However, studies on Clematis mitogenome are rare, thus limiting our full understanding of its phylogeny and genome evolution. Here, we sequenced and annotated the C. acerifolia mt genome using Illumina short- and Nanopore long-reads, characterized the species first complete mitogenome, and performed a comparative phylogenetic analysis with its close relatives. The total length of the C. acerifolia mitogenome is 698,247 bp and the main structure is multi-branched (linear molecule 1 and circular molecule 2). We annotated 55 genes, including 35 protein-coding, 17 tRNA, and 3 rRNA genes. The C. acerifolia mitogenome has extremely unconserved structurally, with extensive sequence transfer between the chloroplast and mitochondrial organelles, sequence repeats, and RNA editing. The phylogenetic position of C. acerifolia was determined by constructing the species mitogenome with 24 angiosperms. Further, our C. acerifolia mitogenome characteristics investigation included GC contents, codon usage, repeats and synteny analysis. Overall, our results are expected to provide fundamental information for C. acerifolia mitogenome evolution and confirm the validity of mitochondrial analysis in determining the phylogenetic positioning of Clematis plants.